The Causal Relationship between Stock Market Indices Volatility and Oil Prices Volatility: Empirical Evidence from Iraqi Stock Exchange - داغر, محمود محمد; صدام, عباس كريم (Journal of Economics and Administrative Sciences, 2018)
The study investigates the relationship between the volatility of the Iraqi Stock Exchange Index (ISX), and the volatility of global oil prices benchmarks, Brent and West Intermediate Texas (WTI), in additional to the Iraqi Oil, Basra Crude Light (BSL) which represents the most exported Iraqi oil and the major influential factor on the Iraqi governmental revenues. Using monthly data covering the period: 1/2005-12/1205, econometrical and technical tools represented by Co-incretion, Vector Error Correction Model – VECM, Granger Causality, and Bollinger band were employed in order to explore the relationship between the variables.The econometric analysis revealed the impact of the oil prices volatility on ISX, while there was no impact of the Iraqi Stock Exchange volatility on crude oil pricing. The analysis also showed that the reliance of ISX performance on Basra crude oil has increased significantly after 2009, proving that oil prices fluctuation is the superior factor that governs the economic activity, which represents the business cycle in Iraq.